Motivations for Sound Symbolism in Spatial Deixis: A Typological Study of 101 Languages - Johansson, Niklas; Zlatev, Jordan (Public Journal of Semiotics, 2013)
We investigated possible motivations for sound symbolism in spatial demonstratives within 101 areally and genetically diverse languages. Six different predictions were formulated on the basis of factors such as (a) semiotic ground (iconic, indexical or combined), (b) speaker-centered, hearer-centered or both and (c) applicable to vowels, consonants or both. Each one of these six predictions resulted in different expected scales of phonemes on the proximal-distal dimension. Languages which conformed to these scales were regarded as motivated (according to a particular prediction). Languages which opposed it were treated as reverse, and if neither was the case, as neutral. The results showed significant motivated/reverse and motivated/neutral ratios only for the prediction based on vowel-frequency, motivated by a combination of iconic and indexical factors, and marginal support for the other predictions concerning vowels. The two predictions based on an assumed link between preverbal vocal pointing and demonstratives also found some, if weaker, support. The only prediction that was completely unsupported concerned the frequency of consonants. The conclusions are that a number of factors combine to motivate sound symbolism in spatial deixis, which appears to involve vowels more than consonants.